Asymmetric systemic risk - Radoslav Raykov; Consuelo Silva-Buston (Bank of Canada, 2022)
Bank regulation is based on the premise that risks spill over more easily from large banks to the banking system than vice versa. On the contrary, we document that risk transmission is stronger in the system-to-bank direction. We term this asymmetric systemic risk, measure it with net exposure metrics, and explore the consequences and channels behind it. We show that banks with positive net exposure to the system had higher default risk during the 2008 crisis, and that bank size and trading activities were the main determinants of this net exposure, which increased default risk through trading income volatility and overall profit volatility. We argue that the current bank supervision objectives can be achieved more efficiently if regulation focuses on reducing such net exposures, rather than buffering the default risks arising from them.
Keywords: G10; G20; 330; Financial institutions; Financial stability; Financial system regulation and policies